A framework for investigating blended learning effectiveness. Issue 2 (2014) - ,; ,; ,
Abstract : Purpose – The move towards "blended learning", consisting of a combination of online and face‐to‐face teaching, continues to gain pace in universities around the world. It is important, however, to question the quality of this learning. The OECD has made use of a model of "Readiness, Intensity and Impact" for investigating the adoption and use of eBusiness technologies. The purpose of this paper is to propose a framework, based on this model and adapted for blended learning, to assess the readiness, intensity of adoption and impact on blended learning offerings. The framework is tested via a description of how one university has adopted and used blended learning, and investigates the quality of the learning from this approach.Design/methodology/approach – The framework is tested via a case study involving the assessment of a blended learning approach to the delivery of a first‐year undergraduate accounting unit at Victoria University, Australia. Various approaches to delivery are assessed over a two‐year period. The results are drawn from a survey specifically designed to identify students' attitudes towards blended learning.Findings – Despite having three new online options readily available for students to access, there was strong support for face‐to‐face delivery methods. In relation to the framework, the assessment suggested that certain aspects of the university's blended learning approach could be investigated further (particularly student readiness for different blended learning options and an overall assessment of the impact of a blended approach), to provide a more holistic view of the readiness to adopt and impact of the blended learning offerings.Originality/value – The value of this contribution lies in the development of a unique framework to assess the impact of blended learning approaches from the viewpoint of student readiness and intensity of separate delivery approaches – whilst maintaining the need to evaluate the effectiveness of blended learning as an overall package.